2017
DOI: 10.1111/his.13106
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and genomic profile of primary sinonasal tract diffuse large B cell lymphoma (DLBCL) reveals gain at 1q31 and RGS1 encoding protein; high RGS1 immunohistochemical expression associates with poor overall survival in DLBCL not otherwise specified (NOS)

Abstract: DLBCL has a characteristic genomic profile. High RGS1 IHC expression associates with poor overall survival in DLBCL .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 72 publications
5
46
0
8
Order By: Relevance
“…Consistently, a Korean study showed only one CNS recurrence among 80 cases of in sinonasal DLBCL (with 30% rate of intrathecal prophylaxis), and no difference in survival with RT, confirming that in the rituximab era neither RT nor routine intrathecal therapy are necessary (Table 2) [69]. Little is known about specific molecular features of DLBCL of the head and neck, except that 80% are non-GCB, with frequent gain of 1q31 (containing RGS1 , 55%) and loss of 9p21.3 (containing CDKN2A , 64%) [70]. Extranodal head/neck location was associated with a better prognosis than nodal DLBCL in population-derived data, but not in clinicopathologic series [2, 14, 4, 68].…”
Section: Prognosis Of Extranodal Dlbcl Arising From Specific Anatomicmentioning
confidence: 95%
“…Consistently, a Korean study showed only one CNS recurrence among 80 cases of in sinonasal DLBCL (with 30% rate of intrathecal prophylaxis), and no difference in survival with RT, confirming that in the rituximab era neither RT nor routine intrathecal therapy are necessary (Table 2) [69]. Little is known about specific molecular features of DLBCL of the head and neck, except that 80% are non-GCB, with frequent gain of 1q31 (containing RGS1 , 55%) and loss of 9p21.3 (containing CDKN2A , 64%) [70]. Extranodal head/neck location was associated with a better prognosis than nodal DLBCL in population-derived data, but not in clinicopathologic series [2, 14, 4, 68].…”
Section: Prognosis Of Extranodal Dlbcl Arising From Specific Anatomicmentioning
confidence: 95%
“…46,47 Immunohistochemistry Immunohistochemical analysis was performed essentially as described previously. A skin sample from a healthy donor and lymph nodes showing reactive hyperplasia were used as a positive and negative control of IL-34 signal, respectively.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…Immunohistochemistry (IHC) staining was performed in an automated system according to the manufacturer's instructions [Leica Bond‐Max and Bond Polymer Refine Detection, DS9800. Novocastra (NV), Leica Microsystems K.K., Tokyo, Japan] . In summary, the staining process consisted on dewax, hydration, antigen retrieval, primary antibody, peroxidase block, postprimary reagent, HRP‐polymer, DAB and hematoxylin steps.…”
Section: Methodsmentioning
confidence: 99%
“…Novocastra (NV), Leica Microsystems K.K., Tokyo, Japan]. 18,19 In summary, the staining process consisted on dewax, hydration, antigen retrieval, primary antibody, peroxidase block, postprimary reagent, HRP-polymer, DAB and hematoxylin steps. Antigen retrieval consisted on Bond ER2 solution for 20 minutes in all the antibodies except for TNFRSF14, CD16 and PTX3 that used Bond ER1 solution.…”
Section: Histologic Disease Activity Assessmentmentioning
confidence: 99%